2015
DOI: 10.1140/epjc/s10052-015-3486-6
|View full text |Cite
|
Sign up to set email alerts
|

Generalized parton distributions and transverse densities in a light-front quark–diquark model for the nucleons

Abstract: We present a study of the generalized parton distributions (GPDs) for the quarks in a proton in both momentum and position spaces using the light-front wave functions (LFWFs) of a quark-diquark model for the nucleon predicted by the soft-wall model of AdS/QCD. The results are compared with the soft-wall AdS/QCD model of proton GPDs for zero skewness. We also calculate the GPDs for nonzero skewness. We observe that the GPDs have a diffraction pattern in longitudinal position space, as seen before in other model… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
53
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
4

Relationship

5
5

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 72 publications
(131 reference statements)
15
53
0
Order By: Relevance
“…However, the transverse densities defined at fixed light-front time have a proper density interpretation [99,100,101]. The charge densities in the transverse impact parameter plane for the nucleon have been discussed extensively in various phenomenological models [63,64,74,102,103,104,105,106,107,108,109], whereas the densities in the transverse coordinate plane have been studied in [110,111,112]. In [113], the deuteron transverse charge density has been evaluated using different parameterizations of the charge form factor and it has been shown that the different parameterizations provide different densities in particular at the center of the impact parameter (b = 0).…”
Section: Introductionmentioning
confidence: 99%
“…However, the transverse densities defined at fixed light-front time have a proper density interpretation [99,100,101]. The charge densities in the transverse impact parameter plane for the nucleon have been discussed extensively in various phenomenological models [63,64,74,102,103,104,105,106,107,108,109], whereas the densities in the transverse coordinate plane have been studied in [110,111,112]. In [113], the deuteron transverse charge density has been evaluated using different parameterizations of the charge form factor and it has been shown that the different parameterizations provide different densities in particular at the center of the impact parameter (b = 0).…”
Section: Introductionmentioning
confidence: 99%
“…According to the standard interpretation [33,52,[65][66][67][68], in the light-cone frame with q + = q 1 + q 3 = 0, the charge and anomalous magnetization densities in the transverse plane can be interpreted with the two-dimensional Fourier transform (FT) of the Dirac and Pauli form factors. Similar to the electromagnetic densities, one can identify the gravitomagnetic density in the transverse plane by taking the FT of the gravitational form factor [41,52].…”
Section: Longitudinal Momentum Densitiesmentioning
confidence: 99%
“…The moments of the structure function and other distributions can then be evaluated as overlaps of the target hadron's light-front wavefunction (LFWF), the hadronic eigensolution of the LF Hamiltonian, as in the Drell-Yan-West formulae for hadronic form factors. [80][81][82][83] The phases of the resulting DIS amplitude and OPE matrix elements reflect the real phase of the stable target hadron's wavefunction. This approximation defines the "static" contribution 54,84 to the measured parton distribution functions (PDF), transverse momentum distributions, etc.…”
Section: Is the Momentum Sum Rule Valid For Nuclear Structurementioning
confidence: 99%